Rhetorical organizations of method chapter in bachelor’s theses by Indonesian TEFL undergraduates - Lubis, Citra Utami; Dalimunte, Ahmad Amin; Nuriatama, Intan; Simbolon, Sulistina Ratulani (Universitas Islam Malang, 2024)
In the scientific realm, the validity of studies and the reliability of empirical findings are of high significance to be presented through research reports, one of which is a thesis. In an undergraduate thesis, the methodology chapter plays an important role in reporting any key details, including research procedures, tools, data collection, and data analysis. Novice writer-researchers such as Indonesian undergraduate students face challenges in writing their methods chapters, one of which deals with the issue of rhetorical organization. Using a genre analysis approach by adopting the comprehensive moves model developed by Chen and Kuo (2012), we analyzed the rhetorical moves in the methods chapters of five Indonesian undergraduate theses. Five bachelor theses in the field of teaching English as a foreign language (TEFL) were selected as data sources due to their relevance to our objectives and predetermined criteria of data selection. The findings show three key moves used in the chapters, with varying frequency. Move 2 was the most frequently used, followed by Move 3, while Move 1 was the least one. Several recurred steps were presented to achieve the communicative purpose of the key moves. Thus, our findings can be useful for Indonesian student writers’ awareness of the importance of utilizing moves and steps in writing and crafting systematic and compelling method chapters.